Block Scheduling Teaching Strategies for the Restructured School Day. - National Science Teachers Association, Arlington, VA.; National Science Teachers Association, Arlington, VA. ([S.l.] : Distributed by ERIC Clearinghouse, 1997)
This book is a compilation of articles taken from the National Science Teachers Association (NSTA) journal entitled "The Science Teacher" that pertain to block scheduling and strategies for effective science instruction within this framework. Articles include "Blockbuster Ideas" (Judy Bohince and Ireve King), "Tackling Block Scheduling" (Martha M. Day and others), "Blocking in Success" (Sylvia L. Cooper), "Year-Round Science" (Marilyn J. Stenvall), "Building Block Schedules" (Janet L. Gerking), "New Class on the Block" (Terrilee Day), "A Lesson in Block Scheduling" (Robert Barnes and others), and "Managing Each Minute" (Michael Clough and others). Also included are a forward and an introduction that relate this new approach to current goals and standards for science education. An invited paper on block scheduling provides background information about the process and its effects on teaching and learning (K. Doug Kissler). (DDR)
Availability: National Science Teachers Association, 1840 Wilson Blvd., Arlington, VA 22201; phone: 1-800-722-NSTA (NSTA Stock No. PB139X).
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Block Scheduling; Educational Change; Educational Innovation; Educational Strategies; Flexible Scheduling; Grouping (Instructional Purposes); Science Activities; Science Curriculum; Secondary Education; Standards; Student Evaluation; Guides, Classroom -- Teacher